2020
DOI: 10.20885/ijcer.vol4.iss1.art4
|View full text |Cite
|
Sign up to set email alerts
|

Development of HOTS (High Order Thinking Skill) Oriented Learning Through Discovery Learning Model to Increase The Critical Thinking Skill of High School Students

Abstract: The aim of this research is to produce HOTS (High Order Thinking Skill) lesson through a valid, practical, and effective discovery learning model for class XI high schools to improve students' critical thinking skills. This research is a development that refers to the Borg & Gall model. The subject trials for grade XI students of SMA Negeri 2 Sangatta Utara, East Kutai. Validity and practicality analysis techniques used percentage of descriptive techniques. The effectiveness analysis technique is by lookin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 0 publications
0
14
0
2
Order By: Relevance
“…LKPD components include LKPD title, Student Identity, Basic Competencies, Learning Objectives, and LKPD Content (Marshel & Ratnawulan, 2020;Pentury et al, 2019). LKPD is one of the means to help and facilitate learning activities so that effective interactions between students and educators will increase student activities in improving thinking skills (Indah, 2020;Marshel & Ratnawulan, 2020). The ability to solve problems that exist in the LKPD will affect the HOTS of students.…”
Section: Discussionmentioning
confidence: 99%
“…LKPD components include LKPD title, Student Identity, Basic Competencies, Learning Objectives, and LKPD Content (Marshel & Ratnawulan, 2020;Pentury et al, 2019). LKPD is one of the means to help and facilitate learning activities so that effective interactions between students and educators will increase student activities in improving thinking skills (Indah, 2020;Marshel & Ratnawulan, 2020). The ability to solve problems that exist in the LKPD will affect the HOTS of students.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, 21st-century education does not only require students to master material content but instead directs them to higher-order thinking skills (Perdana et al, 2017;Ratajczak, 2018). Higher-order thinking skills are a stage of thinking about the cognitive abilities of higher learners (Indah, 2020;Perdana et al, 2017). Higher-order thinking students can solve a problem, discuss a problem, and use students' knowledge in new situations (Ichsan et al, 2019;Turan & Koç, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…HOTS skills are when he is already in the top three levels in the revised Bloom's Taxonomy, namely at the analysis, evaluation, and creation stage (Fadzam & Rokhimawan, 2020). Some previous studies have shown that mastery of HOTS can improve critical thinking skills, creative thinking, logical and reflective thinking (Indah, 2020;King, Goodson, & Rohani, 2010;Yamin, Saputra, & Deswila, 2020;Zulfiani, Suwarna, & Sumantri, 2020).…”
Section: Introductionmentioning
confidence: 99%